Human Resource Resilience in Developing Creative Capabilities to Optimize Digital Transformation - Umi Zunaidah; Rianti Setyawasih; Sitti Usmia; Ris Akril Nurimansjah; Hartanto (Indonesian Journal Economic Review (IJER), 2026)
The purpose of this research is to explain how human resource resilience in developing creative capabilities to optimize digital transformation. The approach taken in this study uses a qualitative approach with the assistance of secondary data as part of the explanatory support within the qualitative approach, which includes relevant books and journal articles. Research results show that human resource resilience is no longer simply the ability to withstand work stress, but rather the primary foundation that drives the ability to optimize digital transformation. In the midst of digital transformation, technology is merely a tool; humans are the driving force behind innovation. To foster this creativity-oriented resilience, management must shift the traditional leadership paradigm toward inclusive and supportive leadership. Leaders need to create a psychologically safe space where every individual feels valued and is not afraid to make mistakes when experimenting with new digital tools. This sense of safety is the primary fuel for the emergence of innovative and out-of-the-box ideas, as true creativity can only thrive in an environment free from the pressure of rigid judgment.